Agri-Food Cooperatives and Strategic Improve in a Rural Development: Qualitative Analysis in Castilla-La Mancha - Ignacio Ruiz Guerra (AECOOP Escuela de Estudios Cooperativos, 2013)
Given the situation we live with a duration unpredictable and unquantifiable consequences at the moment, we must look to the characterization and depth of insight and industry to assist in decision-making cooperatives, taking into account the needs of professionalism they have to undertake. After many years of insisting on this point, the authors continue to argue that the cooperative sector, requires a restructuring that will lead to a professionalization of its dashboards. The realization of this SWOT analysis helps to determine the weaknesses and the opportunities that arise in times of crisis. If the conception we have of the word crisis is negative, in other cultures has a connotation perfectly understandable as positive for being open to new opportunities. Rural development in the municipalities in which they operate these agribusiness cooperatives has much to do with the decisions taken by the dashboards that run them. Every time you perform this type of analysis, scorecards will have a greater availability of information to carry out their work of making decisions, which will result in a better position when facing the difficulties which occur in markets.